THE INFLUENCE OF JOB SATISFACTION ON EMPLOYEE TURNOVER RATE OF PT. INDOMARCO PRISMATAMA (PT. INDOMARET) PALEMBANG - Januar Ida Wibowati; Endang Rahayu; Henson Enjein Manurung (Jurnal Manajemen, 2023)
This study examines the analysis of the effect of job satisfaction on employee turnover rates at PT. Indomarco Prismatama Palembang. The purpose of this research is to determine job satisfaction on the employee turnover rate at PT. Indomarco Prismatama Palembang. The results obtained from the regression analysis using the SPSS version 22 tool indicates that there is an effect of job satisfaction on employee turnover rates at PT. Indomarco Prismatama Palembang., where the results of R in simple linear regression analysis show a correlation between the two independent variables on the dependent variable. The R figure is 0.278, meaning that the correlation between the human resource competency variables is 0.278, this means that there is a strong relationship because the value is close to 1. Meanwhile, the results of R Square (R2) show the value of the coefficient of determination. This figure will be changed to the form of a percentage, which means the percentage of the contribution of the dependent variable. R2 value of 0,